2021
DOI: 10.1002/jcp.30406
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of nucleophosmin (NPM1) in the development of cancer

Abstract: Nucleophosmin (NPM1) is a well-known nucleocytoplasmic shuttling protein that performs several cellular functions such as ribosome biogenesis, chromatin remodeling, genomic stability, cell cycle progression, and apoptosis. NPM1 has been identified to be necessary for normal cellular functions, and its altered regulation by overexpression, mutation, translocation, loss of function, or sporadic deletion can lead to cancer and tumorigenesis. In this review, we focus on the gene and protein structure of NPM1 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 133 publications
1
27
0
Order By: Relevance
“…In the present study, the NPM1 expression in tumors was predicted by bioinformatics analysis, and the expression of NPM1 in LUAD was verified by cell assay and immunohistochemical staining. Through the analysis of Oncomine database, we found NPM1 was overexpressed in 9 types of cancer, and analysis of the TCGA data set found that NPM1 was overexpressed in 13 types of cancer, which was consistent with the results of previous studies (4,36,37). Based on the analysis of GEO and TCGA LUAD data sets, the expression level of NPM1 in LUAD tissues was significantly higher than that in normal tissues.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, the NPM1 expression in tumors was predicted by bioinformatics analysis, and the expression of NPM1 in LUAD was verified by cell assay and immunohistochemical staining. Through the analysis of Oncomine database, we found NPM1 was overexpressed in 9 types of cancer, and analysis of the TCGA data set found that NPM1 was overexpressed in 13 types of cancer, which was consistent with the results of previous studies (4,36,37). Based on the analysis of GEO and TCGA LUAD data sets, the expression level of NPM1 in LUAD tissues was significantly higher than that in normal tissues.…”
Section: Discussionsupporting
confidence: 88%
“…NPM1 is a highly conserved protein commonly found in eukaryotic cells. It is mainly localized in the nucleus and can shuttle between the nucleus and cytoplasm to participate in nucleocytoplasmic signal transport (3,4). Studies have shown that the content of NPM1 in tumor cells and growing cells is significantly higher than that in quiescent cells (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our analysis, NPM1 is not only highly expressed in patients with ES, but is also closely associated with poor patient prognosis and immune infiltration; therefore, the development of drugs targeting NPM1 is essential. NPM1, also known as nuclear phosphoprotein, consists of 294 amino acids and is an abundant and multifunctional nucleolar phosphoprotein that frequently shuttles between the nucleus and the cytoplasm of cells and is involved in a variety of important biological activities (Karimi Dermani et al, 2021). Previous studies have shown that NPM1 plays an important role in cell growth and proliferation by regulating cell cycle progression and centrosome replication (Okuda, 2002).…”
Section: Discussionmentioning
confidence: 99%